Quantum mechanics 500 problems with solutions - Aruldhas, G. (PHI Learning, 2012)
Quantum mechanics is an important area of physics and students of ten find it 'tough' from the understanding point of view. By providing 500 problems with their solutions, Professor Aruldhas, with his expertise in and long experience of teaching the subject, makes the students comprehend the fundamental concepts of Quantum Mechanics with ease. This problem book provides a thorough understanding of the subject and its applications to various physical and chemical problems. The text includes typical problems that illustrate the concepts. It is self-explanatory, comprehensive, and user-friendly. Key Features : Gives, in the beginning of each chapter, an outline of the theory required for solving problems. Includes problems from the simple plug-ins to increasing order of difficulty to strengthen the student's understanding of the subject. Provides many mathematical steps to make the book user-friendly. Gives solutions of problems with different types of potentials including the Dirac delta function potential. Both undergraduate and postgraduate students of physics and chemistry as well as those preparing for the Joint CSIR-UGC test for JRF and other competitive examinations should find this book extremely practical and valuable.